PENGARUH LOKASI USAHA, CITA RASA, DAN HARGA TERHADAP MINAT BELI PRODUK (STUDI PADA KONSUMEN STEAKY STEAK) - Liana, Abel; Annisa, Wahyuni; Mahardika, Djodi; Sanjaya, Vicky F (Journal for Management Student (JFMS), 2023)
This study aims to determine the effect of business location, taste, and price on product purchase intention among Steaky Steak consumers. One of one of the steakhouses that is widely known and often visited by visitors is Steaky Steak. visitors is Steaky Steak. The research was conducted in the month of September 2023 which took place at Steaky Steak with the object of research is Steaky Steak consumers. In this study the authors used type of quantitative approach with data collection methods through questionnaire. The results of this study are expected to provide in-depth insight into the extent to which business location, taste, and price affect product product purchase interest. Steaky Steak should also think about the variables that influence it in order to increase the number of sales. variables that influence it in order to increase the number of sales at Steaky Steak.